Long-term continuous instrumented insole-based gait analyses in daily life have advantages over longitudinal gait analyses in the lab to monitor healing of tibial fractures - Warmerdam, Elke; Wolff, Christian; Orth, Marcel; Pohlemann, Tim; Ganse, Bergita (Frontiers in Bioengineering and Biotechnology, 2024)
Monitoring changes in gait during rehabilitation allows early detection of complications. Laboratorybased gait analyses proved valuable for longitudinal monitoring of lower leg fracture healing. However, continuous gait data recorded in the daily life may be superior due to a higher temporal resolution and differences in behavior. In this study, ground reaction force-based gait data of instrumented insoles from longitudinal intermittent laboratory assessments were compared to monitoring in daily life. Straight walking data of patients were collected during clinical visits and in between those visits the instrumented insoles recorded all stepping activities of the patients during daily life. Out of 16 patients, due to technical and compliance issues, only six delivered sufficient datasets of about 12 weeks. Stance duration was longer (p=0.004) and gait was more asymmetric during daily life (asymmetry of maximal force p<0.001, loading slope p=0.001, unloading slope p<0.001, stance duration p<0.001). This could be caused by a different and more diverse behavior during daily life. The daily life Ggait parameters significantly improved over time with union. One of the patients developed an infected non-union and showed worsening of force-related gait parameters, which was earlier detectable in the continuous daily life gait data compared to the lab data. Therefore, continuous gait monitoring in the daily life has potential to detect healing problems early on. Continuous monitoring with instrumented insoles has advantages once technical and compliance problems are solved.